The fate of backwardness: Portuguese expectations over modernity - Frois, Catarina (Anthropological Journal of European Cultures, 2012)
In Portugal, terms such as 'modernisation', 'progress' and 'development' are continually invoked by a wide range of social actors, representing the right path and ultimate goal of all political and social change, but on the other hand conceal the actual truth that, to use Latour's expression: 'We have never been modern'. The result is that the demand for modernisation is accompanied by the parallel reifi cation of 'backwardness'. Alluding to Portugal's peripheral condition, to its distance from the rest of Europe and so forth, is part of common everyday discourse, and the country is typically portrayed as a kind of European backwater, forever lagging behind more advanced states. This article aims to present and discuss how backwardness and modernisation are recurrently present in political discourse as a leitmotiv for social, economic and cultural change and the way it is incorporated into a broader and rooted self-representation of the Portuguese modus vivendi and national features.